2017
DOI: 10.1055/s-0037-1604436
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Enteral Feeding After Necrotizing Enterocolitis

Abstract: Initiating early enteral feeding, within 5 days of NEC diagnosis, is not associated with adverse outcomes, including NEC recurrence. In addition, catheter-related sepsis and post-NEC stricture rates were unchanged between early and delayed enteral feeding groups after NEC. However, the quality of the evidence from the review of literature is suboptimal. A further RCT is needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
(36 reference statements)
0
10
0
4
Order By: Relevance
“…Three retrospective or change in practice studies [ 12 , 14 , 15 ] and one meta-analysis [ 16 ] met our inclusion criteria. A previous meta-analysis by Hock et al [ 16 ] included only two of the three studies we identified as eligible for this current meta-analysis. The third single-center study [ 12 ] was published after the Hock et al [ 16 ] meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three retrospective or change in practice studies [ 12 , 14 , 15 ] and one meta-analysis [ 16 ] met our inclusion criteria. A previous meta-analysis by Hock et al [ 16 ] included only two of the three studies we identified as eligible for this current meta-analysis. The third single-center study [ 12 ] was published after the Hock et al [ 16 ] meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A previous meta-analysis by Hock et al [ 16 ] included only two of the three studies we identified as eligible for this current meta-analysis. The third single-center study [ 12 ] was published after the Hock et al [ 16 ] meta-analysis. The Hock et al meta-analysis included a total of 91 patients with 56 infants in the earlier enteral feeding group after NEC diagnosis and 35 infants in the later feeding group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Также одним из наиболее часто описываемых краткосрочных неблагоприятных исходов НЭК является реци-див данного состояния, который развивается между 3-й и 4-й неделями после первоначального эпизода НЭК на фоне полного установления энтерального питания [14]. Существует несколько гипотез о патогенезе рецидива НЭК.…”
unclassified
“…Следует отметить, что эффективность и безопасность раннего трофического питания была изучена в работах, касающихся начала энтеральной поддержки как меры профилактики дебюта НЭК у недоношенных детей, а не его возобновления после диагностированного НЭК. На основании вышеизложенного вопрос, как рано после НЭК необходимо начинать энтеральное питание, пока остается дискуссионным и открытым, а порог обеспокоенности относительно отсутствия данных рекомендаций обусловлен значимой распространенностью рецидива НЭК, составляющего 4-10% среди всех случаев НЭК, и остается высоким [14,[26][27][28][29][30].…”
unclassified